Navigating Classroom Management : Experiences of expatriate teachers in UAE international schools - Wijekoon Mudiyanselage, Randima Hiyanthi Wijekoon (My University, 2026)
Increasing cultural diversity in international schools may introduce new classroom management challenges to expatriate teachers, those who come from different cultural backgrounds. Despite the growth of international schools in the United Arab Emirates(UAE), few studies have explored expatriate teacher experiences with regards to classroom management challenges and strategies within culturally diverse classrooms. In order to address that gap, current study explores the classroom management challenges faced by expatriate teachers, and the strategies they use to overcome such situations. Moreover, the study is guided by Culturally Responsive Classroom Management(CRCM) of Weinstein et al. (2004). This study employs a qualitative design, conducting semi-structured interviews with six expatriate teachers from UAE international schools, and the collected data was analyzed using Thematic analysis method.Data analysis resulted in several themes which emerged as classroom management challenges faced by expatriate teachers including cultural and linguistic diversity, student behavior challenges, managing students with special educational needs (SEN), family and socioeconomic influences, and institutional and structural constraints. The analysis also revealed that expatriate teachers employ several classroom management practices when managing diverse classrooms in UAE international schools including, developing an understanding of student and their background, adapting their teaching practices and learning activities, building positive teacher student relationships, managing student behavior, and collaborating with colleagues and parents. Together, the findings of current study revealed that classroom management in UAE international schools is shaped by teachers’ cultural awareness, collaborative skills, adaptive and flexible teaching practices, and relationship building. Furthermore, this study underscores the importance of CRCM as a lens for examining and enhancing classroom management practices in culturally diverse international school contexts.
Keywords: international schools; expatriate teachers; classroom management; multicultural classrooms; culturally responsive classroom management